Poly(vinylidene fluoride) and copolymers as porous membranes for tissue engineering applications - Pereira, Eduardo Jorge Nunes (2015)
Poly(vinylidene fluoride) (PVDF) and its main copolymers - poly(vinylidene fluoride-co-hexafluoropropene), P(VDF-HFP), and poly(vinylidene fluoride-co-trifluoroethylene), P(VDF-TrFE) - were processed by solvent casting at room temperature in the form of porous membranes. Copolymer membranes showed higher degree of porosity than PVDF, the average pore size being larger for P(VDF-TrFE) than for P(VDF-HFP) and PVDF. All membranes show high hydrophobicity with water contact angles in the range 94° to 115°, and electroactive beta phase contents above 90%. The adhesion and proliferation of both C2C12 myoblast and MC3T3-E1 pre-osteoblast cells on the membranes were investigated. It is demonstrated that PVDF membranes promote higher cell proliferation while P(VDF-HFP) membranes show the lowest proliferation for both kinds of cell. The proliferation on P(VDF-TrFE) membranes is cell dependent, higher for MC3T3-E1 cells but lower for C2C12 cells, related to the effect of the highly porous structure on the preferred morphology of each cell type, as the higher pore size and porosity of the P(VDF-TrFE) membrane induce cell elongation, which is preferred just by the C2C12 muscle cells.